Analisis Formula Nugget Tahu, Ubi Jalar Kuning, Brokoli Untuk Balita Wasting - Umasangaji, M. Sadli; Theresia, Theresia; Fajar, Ibnu (NUTRITURE JOURNAL; Vol 2 No 1 (2023): Jurnal Nutriture, 2023)
Background: Wasting is a toddler problem related to inadequate nutritional intake and the presence of comorbidities or infectious diseases. thing as a direct cause. Wasting was assessed using the anthropometric index of Body Weight by Height or Body Length with a z-score value below -2 SD. Riskesdas data in 2018 describes very thin toddlers as much as 3.5% and skinny toddlers as much as 6.7%. The combined data of very thin + skinny toddlers is 10.2%. In overcoming wasting, this nugget was made with the aim of this research being to analyze the nutritional quality, protein quality, organoleptic test and determine the best treatment level for the tofu, yellow sweet potato and broccoli nuggets formula. Methods: This research is an experimental study that uses a completely randomized design on the Tofu Nugget Formula, Yellow Sweet Potato and Broccoli. The proportion of the treatment level of this Nugget with the ratio of Tofu: Yellow Sweet Potato: Broccoli is P1 (40: 30: 30), P2 (50: 20: 30), P3 (50: 30: 20). Results: Determination of the level of treatment shows that the best value is treatment 3 (P3) with a value of 0.71. The nutritional values ??for treatment 3 (P3) were 96.50 Cal of energy, 3.15 grams of protein, 4.78 grams of fat, 10.38 grams of carbohydrates, 63.38 mg of phosphorus and 4.53 mg of vitamin C. The organoleptic results for P3 were color 3.7, aroma 3.75, taste 3.3, texture 3.05. Conclusion: Organoleptically, each aspect of color, aroma, taste and texture showed no difference (p value > 0.05). While the composition of all nutritional values ??contained different values ??from each treatment.   Keywords: Formula, Nugget, Tofu, Wasting